Perspektif Konstruktivisme dalam Bantuan Luar Negeri Australia ke Otoritas Palestina - Irza Khurun’in (Jurnal Transformasi Global, 2015)
Abstract In the end of 2007, Australia through AusAID increased their foreign aid to the Pelstinian Authority nearly tripled, from $ 15.2 million in 2006-2007 to $ 42 million in 2007-2008. That policy could not be separatedfrom the Australian interest in the political conflictconstellation betweenIsraeland Palestine. Yet, as a donor country, Australia didn’t get economically benefit from the aid flow to Palestine. Moreover, the geographical location between two countries are very far apart. Furthermore, Australian aid to Palestinian Authority is also inconsistentwith thepolitical support, such as Australia rejection on the recognition ofPalestinian sovereignty. So, the research question is ‘why did Australia increaseits foreignaidtothe Palestinian Authority?’ To analyze this Australia’s behavior, the author uses a constructivist approach, with emphasize on humanitarian norm and Australian identity as a donor country. The basic assumption of constructivism focused on ideational structure and it become the main framework in this paper. Main argument in this paper is international humanitarian norm and Australian identity as a donor country act as ideational structure whichconstitutively interplay on the Australian policy toincrease foreign aid to the Palestinian Authority. Keywords: International humanitarian norm, national identity, foreign aid